Phycospheric Native Bacteria Pelagibaca bermudensis and Stappia sp. Ameliorate Biomass Productivity of Tetraselmis striata (KCTC1432BP) in Co-cultivation System through Mutualistic Interaction - Park, Jungsoo; Park, Bum Soo; Wang, Pengbin; Patidar, Shailesh K.; Kim, Jin Ho; Kim, Sae-Hee; Han, Myung-Soo (Frontiers in Plant Science, 2017)
Effective sustainable algal cultivation techniques are essential for mass production of the marine microalga Tetraselmis for biofuel and array of co-products. The phycospheric communities affect the microalgal growth and metabolism through various allelochemical and nutrient interactions; hence, their potential to affect the quantity and quality of both biomass and bioproducts is significant. In the present study, we have screened the phycospheric communities of biofuel producing Tetraselmis striata (KCTC1432BP). A total of 26 bacterial strains were isolated and identified from the phycosphere of Tetraselmis striata mass culture. Then, each bacterial strain was tested in co-cultivation conditions with Tetraselmis striata for evaluating its growth promoting and inhibitory effects. Among these all strains, two promising strains (Pelagibaca bermudensis KCTC 13073BP and Stappia sp. KCTC 13072BP) were selected because of their maximum growth promoting effects and mutualistic interactions. The growth rate, biomass productivity, lipid contents and fatty acids were analyzed during their combined growth in O3 media and compared with axenic growth of Tetraselmis striata. Later, growth promoting mechanisms in the co-cultivation environment were investigated for these promising bacterial strains under replete and limited conditions of nutrients (nitrate, phosphate and vitamin B12). The growth promoting potential of P. bermudensis was illustrated by the two fold enhancement in biomass productivity. These bacteria are promising for microalgal cultivation without any negative effects on the native seawater bacterial communities, as revealed by NGS analysis. This study represents, to date, the first report highlighting the role of phycospheric growth promoting bacteria of promising biofuel feedstock Tetraselmis striata.